Developing evidence-informed principles for trauma-aware pedagogies in physical education. (4th July 2022) - Quarmby, Thomas; Sandford, Rachel; Green, Rachael; Hooper, Oliver; Avery, Julie
ABSTRACT: Background : More and more children are experiencing what have been termed adverse childhood experiences. An individual's response to these stressful events determines whether or not they are considered traumatic – whereby the experience is so overwhelming that it engulfs their coping mechanisms leading to lasting negative effects on wellbeing. Notably, childhood trauma is now recognised as a global health epidemic. Physical education (PE) is a unique context whereby participation is public, and the body plays a central role. Our work with care-experienced young people (who are likely to have experienced trauma) tells us that the depth of vulnerability felt by students who have been exposed to trauma is unlikely to be fully be recognised by PE teachers. Purpose : This paper therefore seeks to enhance practitioners' understanding of how trauma manifests and the impact it can have on children and young people's engagements in PE. It is driven by two key questions. First, why is it important for physical educators to have an awareness and understanding of trauma? Second, what principles might underpin trauma-aware pedagogies for PE? Discussion : We note how childhood trauma has been found to consistently impact neurological, physiological and psychological development. Understanding the impact of trauma, and the responses it might evoke, is beneficial for those working with/for children and young people so as to help them comprehend the underlying reasons why some children and young people have difficulties with learning, building relationships and managing behaviour. In an effort to help mitigate the impact of trauma and prevent re-traumatisation, drawing on our collective experiences of working with care-experienced youth and practitioners in PE, physical activity and sport-related contexts, we suggest that the following five evidence-informed principles might be helpful when seeking to enact trauma-aware practice: (1) ensuring safety and wellbeing, (2) establishing routines and structures, (3) developing and sustaining positive relationships that foster a sense of belonging, (4) facilitating and responding to youth voice and, (5) promoting strengths and self-belief. Conclusion : The principles we identify all point to the need for creating safe environments, shaped by consistency, positive connections and opportunities for interaction and engagement. It is not our intention, however, to suggest that there is only one way to enact a trauma-aware pedagogy, rather that an understanding of trauma may enable physical educators to ask when, and for whom, it might be best to draw on particular models in the teaching of PE, through which these principles can be applied.